Religion and theology a guide to current reference resources - McIntosh, Lawrence D.; Charles Sturt University Centre for Information Studies Riverina, NSW (Wagga Wagga, N.S.W. Centre for Information Studies, Charles Sturt University, 1997)
Includes index.
Keywords: Religion -- bibliography; Theology -- bibliography